Does the need for uniqueness lead to non-suicidal self-injury? The mediation of depression and the moderation of gender - Zhang, Xian; Cao, Wanjun; Fang, Jiashuai; Hu, Dongxu (Frontiers in Public Health, 2023)
Objective Based on the integrated theoretical model of the development and maintenance of non-suicidal self-injury (NSSI) and gender role theory, this study investigated the longitudinal impact of the need for uniqueness on NSSI among adolescents, and the mediating role of depression and the moderating role of gender. Participants A total of 1,166 middle school students (Mean age = 13.04, SDage = 0.78, range = 11–16) from a city in central China was recruited to complete the Need for Uniqueness Scale, Depression Scale, and Adolescent Self-Injury Questionnaire at two waves. The participants included 475 boys and 457 girls. Methods Convenience sampling was used, and a longitudinal study (2 time points with a 6-month interval) was conducted to test our hypotheses. SPSS 25.0 was used to evaluate reliability, and to calculate descriptive statistics and Pearson correlation. PROCESS version 3 was used to test longitudinal relationships among the need for uniqueness, depression and NSSI, and construct a moderated mediation model. Results Results revealed that T1 need for uniqueness in adolescents was significantly positively associated with T2 NSSI and T2 depression, and T2 depression was significantly positively associated with T2 NSSI. After controlling for gender, T1 need for uniqueness positively predicted T2 NSSI. Furthermore, the mediation analysis demonstrated that the pathway linking T1 need for uniqueness to T2 NSSI through T2 depression was statistically significant. Moreover, gender moderated the indirect effect from T2 depression to T2 NSSI in the association between T1 need for uniqueness and T2 NSSI. Compared to boys in the same situation, girls who are susceptible to depression were more likely to commit NSSI. Conclusion This study demonstrated that the need for uniqueness in adolescents longitudinally predicts NSSI through the mediating role of depression and gender moderates the indirect effect from depression to NSSI. The current study not only suggests that the need for uniqueness is a risk factor for NSSI among adolescents, but also provides an empirical basis for the prevention and intervention of NSSI.